2006
DOI: 10.1002/eji.200636187
|View full text |Cite
|
Sign up to set email alerts
|

Alternating vector immunizations encoding pre‐erythrocytic malaria antigens enhance memory responses in a malaria endemic area

Abstract: A heterologous prime-boost strategy has been developed to potently induce T cell responses to pre-erythrocytic malaria antigens. Efficacy in the field is likely to depend on both peak immunogenicity and the durability of responses. To improve both immunogenicity and durability of responses, 54 adult males from a malaria endemic area were immunized with different vaccination regimens, systematically varying antigenic insert and the number and sequence of component vaccinations. The component vaccinations were r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 22 publications
0
17
0
Order By: Relevance
“…In malaria-exposed volunteers, the alternating-vector vaccinations with the ME-TRAP insert provoked a rise in ex vivo IFN-␥ production and resting memory cells (2 ; P ϭ 0.07). However, although FP9/MVA regimens encoding CS generated a rise in IFN-␥ (2), there was no evidence of a rise in IL-2 production (P ϭ 0.6).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In malaria-exposed volunteers, the alternating-vector vaccinations with the ME-TRAP insert provoked a rise in ex vivo IFN-␥ production and resting memory cells (2 ; P ϭ 0.07). However, although FP9/MVA regimens encoding CS generated a rise in IFN-␥ (2), there was no evidence of a rise in IL-2 production (P ϭ 0.6).…”
Section: Resultsmentioning
confidence: 99%
“…However, experiments that selectively depleted CCR7-positive T cells before culture suggest that the cultured ELISPOT assay does detect central memory cells (14). In previous studies, we have shown that resting memory cells are expanded following vaccination in malaria-na ïve subjects (19) and malaria-exposed subjects (2) and are not simply due to prior exposure.…”
mentioning
confidence: 80%
See 2 more Smart Citations
“…Although the mouse in general and our approach specifically may have limitations as a preclinical model, the results still may have relevance for understanding why subunit vaccines that evoke sterilizing immunity against human malaria have been difficult to obtain. For example, accumulating data from human clinical trials show that current prime-boost immunizations generate Plasmodium-specific T cell responses in the range of 0.1% of PBL at the peak after boosting and Ͻ0.01% at memory stages (20,(33)(34)(35)(36). These frequencies are 10-fold and 100-fold lower than required to protect mice from Plasmodium infection and consist mainly of CD4 T cells, which may explain why these vaccines delay the onset but rarely prevent blood-stage parasitemia (20,36).…”
Section: Discussionmentioning
confidence: 99%